Mesenchymal tumors of the urinary bladder - Agaimy, Abbas; Hartmann, Arndt (Pathologe, 2016)
Mesenchymal tumors and tumor-like lesions of the urinary bladder are rare. They encompass a heterogeneous group of reactive pseudosarcomatous tumor-like changes and benign neoplastic lesions as well as malignant neoplasms (sarcomas) with variable biological behavior. The well-known differential diagnostic difficulties related to these conditions are mainly due to their rarity and thus limited experience and familiarity with their histological features and due to the significant morphological overlap between fully benign reactive conditions and aggressive malignant neoplasms. The distinction between them may on occasion represent a real challenge and is associated with several pitfalls. This overview summarizes the clinicopathological and differential diagnostic aspects of the most important lesions and discuss their differential diagnosis in the light of current knowledge.
EVALuna2:6784